Mempertimbangkan Fenomena Populisme Islam di Indonesia dalam Perspektif Pertarungan Diskursif: Kontestasi Wacana Politik Antara Gerakan Nasional Pengawal Fatwa Ulama (GNPF-Ulama) dan Nahdlatul Ulama (NU) - Dian Dwi Jayanto (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2019)
This study argues that National Movement of Fatwa Guards-Ulama (GNPF-Ulama) is not the sole political representation of Indonesian Muslim power at the moment, as the main analysis unit when discussing the phenomena of Islamic populism in Indonesia. Nahdlatul Ulama strives to retrieve discourse of Indonesian Islamic populism from GNPF-Ulama. NU's efforts to reinforce its position as an Islamic political power are triggered by evaluation that the resurgence of earlier populis movement has affected NU’s influence as the dominant organization in Indonesia. In line with this argument, discourse analysis on the importance of Indonesian Muslims mobilization for political purposes can be applied both as a theoretical and ideological framework, in addition to the study of populism and Islamic populism. On the other hand, Islamic identity based populism can be understood as one of the models which in contrast with populism based on nationalism. Conversely, the effort to unite nationalism and Islam has become Nu’s agenda to revoke GNPF-Ulama’s popuslis narrative. In spite of differences in religious ideology, the discussion of Islamic populism is arising out of the narrative contestation occurring within the internal Muslims itself. Finally, this study offers a reading of the phenomena of Islamic populism in the context of discourse.